“Late” regressions of metastases from renal cancer after a period of disease progression continuing the same intermittent low dose immunotherapy regimen - Giacosa, R.; Santi, R.; Vaglio, et al., A. (Acta Biomedica Atenei Parmensis, 2004)
We here describe two patients with metastatic renal cell cancer (mRCC) treated with immunotherapy in whom the metastases completely regressed after a period of progressive disease. The treatment schedule was based on repeated cycles of low-dose recombinant interleukin-2 and recombinant interferon-α, and was never changed during the course of the disease. The first patient received immunotherapy because of multiple bilateral lung metastases. Progressive disease, with mediastinal lymph node involvement and an increased number of lung metastases, was observed after 30 months of regularly repeated therapy; complete regression was achieved after 60 months of immunotherapy (after 16 immunotherapy cycles). The second patient began immunotherapy because of three small lung metastases. Disease progression was observed after three cycles, but complete regression was obtained about 16 months after the start of immunotherapy (after 5 immunotherapy cycles). Long-term low-dose immunotherapy may bring about an effective anti-tumour response even late in the course of the disease and after an initial disease progression.